PERANCANGAN APLIKASI PEMBELAJARAN KRIPTOGRAFI PADA ALGORITMA DATA ENCRYPTION SYSTEM (DES) MENGGUNAKAN METODE COMPUTER ASSISTED INTRUCTION - OKTARIA, RISKA (STMIK KAPUTAMA, 2019)
Learning is the process of interaction of students with educators and learning resources in a learning environment. Learning is assistance provided by educators so that an agreed process of knowledge and knowledge can occur, mastery of proficiency and character, and formation of attitudes and beliefs in students. In other words, learning is a process to help students learn well. Cryptography is a study of mathematical techniques related to aspects of information security, such as confidentiality data, validity data, integrity data, and authentication data. All information about information security can be regulated by cryptography. Cryptography can be interpreted as a science or senior for securing messages. Computer Assisted Instruction (CAI) is a system for delivering microprocessor-based subject matter that is designed and programmed into the system. Computer Assisted Instruction (CAI) defines as the use of computers in completing agreed materials with students actively and allows feedback